2020
DOI: 10.1126/sciadv.abc1992
|View full text |Cite
|
Sign up to set email alerts
|

Nebulin and Lmod2 are critical for specifying thin-filament length in skeletal muscle

Abstract: Regulating the thin-filament length in muscle is crucial for controlling the number of myosin motors that generate power. The giant protein nebulin forms a long slender filament that associates along the length of the thin filament in skeletal muscle with functions that remain largely obscure. Here nebulin’s role in thin-filament length regulation was investigated by targeting entire super-repeats in the Neb gene; nebulin was either shortened or lengthened by 115 nm. Its effect on thin-filament length was stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(64 citation statements)
references
References 50 publications
5
59
0
Order By: Relevance
“…Instead, it has been suggested that nebulin contributes to the regulation of the Z-disk width ( Witt et al, 2006 ; Li et al, 2015 ). This is supported by the correlation between the number of nebulin Z-repeats and the Z-disk width that has been found ( Kiss et al, 2020 ) and the widened Z-disks that locally exist in nebulin-deficient muscle ( Witt et al, 2006 ; Tonino et al, 2010 ; Li et al, 2015 ).…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations
“…Instead, it has been suggested that nebulin contributes to the regulation of the Z-disk width ( Witt et al, 2006 ; Li et al, 2015 ). This is supported by the correlation between the number of nebulin Z-repeats and the Z-disk width that has been found ( Kiss et al, 2020 ) and the widened Z-disks that locally exist in nebulin-deficient muscle ( Witt et al, 2006 ; Tonino et al, 2010 ; Li et al, 2015 ).…”
Section: Introductionmentioning
confidence: 62%
“…Owing to alternative splicing events in the Z-repeat region and in super-repeat 12, there are often multiple annotated nebulin splice variants. Because gel electrophoresis and gene expression data from mice indicate that the majority of transcripts include all annotated super-repeat and Z-repeat exons ( Kiss et al, 2020 ), the longest isoform was selected for further analysis. Species were chosen based on completeness of the nebulin genomic sequence, as reflected by the absence of gaps that might indicate missing exons in the annotation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, muscle viability and proliferative status were evaluated using fast and slow myosin protein staining. These proteins represent proliferative and apoptotic muscle cells, respectively 55 . The findings show that muscle structure atrophy is alleviated and muscle viability is increased significantly.…”
Section: Discussionmentioning
confidence: 99%